Cordilleran front range structural features in northwest Montana interpreted from vintage seismic reflection data. (April 2016) - Porter, Mason C.; Rutherford, Bradley S.; Speece, Marvin A.; Mosolf, Jesse G.
Abstract: Industry seismic reflection data spanning the Rocky Mountain Cordillera front ranges of northwest Montana were reprocessed and interpreted in this study. Five seismic profiles represent 160 km of deep reflection data collected in 1983 that span the eastern Purcell anticlinorium, Rocky Mountain Trench (RMT), Rocky Mountain Basal Décollement (RMBD), and Lewis thrust. The data were reprocessed using modern techniques including refraction statics, pre-stack time migration (PSTM), and pre- and post-stack depth migration. Results indicate the RMBD is 8–13 km below the Earth's surface and dip 3–10° west. Evidence for the autochthonous Mesoproterozoic Belt and basal Cambrian rocks beneath the RMBD is present in all of the profiles and appears to extend east of the RMT. The Lewis thrust was identified in the seismic profiles and appears to sole into the RMBD east of the RMT. The RMT fault system has a dip displacement of 3–4 km and forms a half graben filled with 1 km of unconsolidated Tertiary sedimentary deposits. The RMT and adjacent Flathead fault systems are interpreted to be structurally linked and may represent a synthetic, en echelon fault system. Highlights: The Rocky Mountain Trench (RMT) fault system has a dip displacement of 3–4 km. The RMT reactivated a major décollement ramp. The RMT and adjacent Flathead fault systems are structurally linked. Autochthonous Belt and Cambrian rocks are underneath the basal décollement.